Learned – spoken: Manglish / Muhammad Iyaz Hariz Muhammad Rizal and Sheik Badrul Hisham Jamil Azhar - Muhammad Rizal, Muhammad Iyaz Hariz; Jamil Azhar, Sheik Badrul Hisham (Academy of Language Studies, 2023)
Malaysian English or Manglish is one of many good examples of a creole language; where the base language, English, is integrated and mixed with several local languages such as Malay, Hokkien, Mandarin, Cantonese, and Tamil, creating a new English that is nativised. Through the birth of Manglish, a language barrier was formed between Manglish speakers and native English speakers. Through this, it was found that in Malaysia, the English that is learnt and taught in formal education differs greatly with the English that is spoken. In the form of flashcards, this paper strives to uncover these differences, and shed light on the likely derivations behind each ‘Manglish’ term. Despite being a creole of many different languages fused within English, this particular paper focused mainly on Malay influences.